Simulation of the part load behavior of combined heat pump-organic rankine cycle systems - Eppinger, Bernd; Muradi, Mustafa; Scharrer, Daniel; Zigan, Lars; Bazan, Peter; German, Reinhard; Will, Stefan (Energies, 2021)
Pumped Thermal Energy Storages (PTES) are suitable for bridging temporary energy shortages, which may occur due to the utilization of renewable energy sources. A combined heat pump (HP)-Organic Rankine Cycle (ORC) system with suitable thermal storage offers a favorable way to store energy for small to medium sized applications. To address the aspect of flexibility, the part load behavior of a combined HP-ORC system, both having R1233zd(E) (Trans-1-chloro-3,3,3-trifluoropropene) as working fluid and being connected through a water filled sensible thermal energy storage, is investigated using a MATLAB code with integration of the fluid database REFPROP. The influence on the isentropic efficiency of the working machines and therefore the power to power efficiency (P2P) of the complete system is shown by variation of the mass flow and a temperature drop in the thermal storage. Further machine-specific parameters such as volumetric efficiency and internal leakage efficiency are also considered. The results show the performance characteristics of the PTES as a function of the load. While the drop in storage temperature has only slight effects on the P2P efficiency, the reduction in mass flow contributes to the biggest decrease in the efficiency. Furthermore, a simulation for dynamic load analysis of a small energy grid in a settlement is conducted to show the course of energy demand, supplied energy by photovoltaic (PV) systems, as well as the PTES performance indicators throughout an entire year. It is shown that the use of PTES is particularly useful in the period between winter and summer time, when demand and supplied photovoltaic energy are approximately equal.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Carnot battery; Fluid mass flow; Part load; Simulation; Temperature; Thermal energy storage